Comparative Analysis of Three Trypanosomatid Catalases of Different Origin - Ľubomíra Chmelová; Claretta Bianchi; Amanda T. S. Albanaz; Jana Režnarová; Richard Wheeler; Alexei Yu. Kostygov; Natalya Kraeva; Vyacheslav Yurchenko (Antioxidants, 2021)
Most trypanosomatid flagellates do not have catalase. In the evolution of this group, the gene encoding catalase has been independently acquired at least three times from three different bacterial groups. Here, we demonstrate that the catalase of Vickermania was obtained by horizontal gene transfer from Gammaproteobacteria, extending the list of known bacterial sources of this gene. Comparative biochemical analyses revealed that the enzymes of V. ingenoplastis, Leptomonas pyrrhocoris, and Blastocrithidia sp., representing the three independent catalase-bearing trypanosomatid lineages, have similar properties, except for the unique cyanide resistance in the catalase of the latter species.